Skin Abscess due to Serratia marcescens in an Immunocompetent Patient after Receiving a Tattoo - J. Diranzo García; J. Villodre Jiménez; V. Zarzuela Sánchez; L. Castillo Ruiperez; A. Bru Pomer (Case Reports in Infectious Diseases)
The incidence of skin infections caused by Serratia marcescens is extremely low and such infections are typically observed in immunocompromised patients. The clinical manifestations of these infections include cellulitis, abscesses, fluctuant nodules, or granulomatous lesions. Infections caused by S. marcescens are very difficult to treat due to their resistance to many antibiotics, which often leads to specific and prolonged treatment. Infections after receiving a tattoo are very rare and are caused by unhygienic conditions or the inexperience of the tattooist. In this paper we present the case of a 32-year-old male with no comorbidity, who presented an abscess caused by S. marcescens in a area that was tattooed one month earlier. The case was resolved with surgery and antimicrobial therapy that was based on the antibiogram. To our knowledge, this is the first reported case of a S. marcescens skin infection following a tattoo, in the absence of immunosuppression.